The Structure, Evolution, and Gene Expression Within the Caprine Leukocyte Receptor Complex - Schwartz, John C.; Sanderson, Nicholas D.; Bickhart, Derek M.; Smith, Timothy P. L.; Hammond, John A. (Frontiers in Immunology, 2019)
The leukocyte receptor complex (LRC) encodes a large number of immunoglobulin (Ig)-like receptors involved in innate immunity, particularly in modulating natural killer (NK) cell function. Within the LRC, the killer cell Ig-like receptors (KIR), the leukocyte Ig-like receptors (LILR), and a recently described novel Ig-like receptor family are highly variable between species, which is consistent with strong selection pressure. Among the species studied to date, only simians (such as humans) and bovids (such as cattle and goats) have an expanded complement of KIR genes, making the latter group an interesting model for studying KIR evolution. Therefore, using recent highly-contiguous genome assemblies and an assembly of bacterial artificial chromosomes, we presently describe the structure of the LRC, and the KIR region in particular, in sheep and goats. These species diverged from a common ancestor approximately 10 million years ago and from cattle approximately 25 million years ago. We identified the presence of conserved KIR genes common to both goats and sheep and confirm a partial sheep haplotype shared between the Rambouillet and Texel breeds. Goats and sheep have independently expanded two novel KIR subgroups, and unlike cattle or any other mammal, they do not appear to possess a functional 3DL-lineage KIR gene. Investigation of LRC gene expression using available transcriptomic data for various sheep and goat tissues revealed that a relatively conserved caprine-specific KIR subgroup is expressed in macrophages. The LILR and novel Ig-like receptors were also highly expressed across a diverse range of tissues. This further step towards our understanding of the NK cell receptor repertoire will help inform future studies investigating immune response variation in these species.